1999
DOI: 10.1139/w98-224
|View full text |Cite
|
Sign up to set email alerts
|

Growth and survival of uninjured and sublethally heat-injured Escherichia coli O157:H7 on beef extract medium as influenced by package atmosphere and storage temperature

Abstract: The effect of atmospheric composition and storage temperature on growth and survival of uninjured and sublethally heat-injured Escherichia coli O157:H7, inoculated onto brain heart infusion agar containing 0.3% beef extract (BEM), was determined. BEM plates were packaged in barrier bags in air, 100% CO2, 100% N2, 20% CO2: 80% N2, and vacuum and were stored at 4, 10, and 37 degrees C for up to 20 days. Package atmosphere and inoculum status (i.e., uninjured or heat-injured) influenced (P < 0.01) growth and surv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2000
2000
2012
2012

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 18 publications
(19 reference statements)
0
3
0
1
Order By: Relevance
“…Not only the growth conditions prior to heat treatment, but also those after heating will in¯uence survival of bacterial cells. After heat treatment many cells will be sublethally injured, as can be observed by the substantial delay in detecting growth of heat-treated bacterial cells compared with unheated cells (D'Aoust 1978;Meylan et al 1996;Keswani and Frank 1998;Semanchek et al 1999). Hence, recovery of injured MAP cells in an appropriate medium after heat treatment is very important and may in¯uence MAP survival counts (Damato and Collins 1990;Keswani and Frank 1998).…”
Section: Strains and Culture Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Not only the growth conditions prior to heat treatment, but also those after heating will in¯uence survival of bacterial cells. After heat treatment many cells will be sublethally injured, as can be observed by the substantial delay in detecting growth of heat-treated bacterial cells compared with unheated cells (D'Aoust 1978;Meylan et al 1996;Keswani and Frank 1998;Semanchek et al 1999). Hence, recovery of injured MAP cells in an appropriate medium after heat treatment is very important and may in¯uence MAP survival counts (Damato and Collins 1990;Keswani and Frank 1998).…”
Section: Strains and Culture Conditionsmentioning
confidence: 99%
“…After heat treatment many cells will be sublethally injured, as can be observed by the substantial delay in detecting growth of heat‐treated bacterial cells compared with unheated cells (D’Aoust 1978; Meylan et al . 1996; Keswani and Frank 1998; Semanchek et al . 1999).…”
Section: Critical Parameters In Heat Inactivation Experimentsmentioning
confidence: 99%
“…E.coli O157:H7 can also survive well during frozen storage of beef, chicken, and water at temperatures as low as -80°C and at -20°C for as long as 9 months . In addition, various studies have demonstrated that the organism is also resistant to nitrate, sodium chloride, alkaline environments, and modified atmosphere (Glass et al, 1992;Semanchek et al, 1999).…”
Section: Characteristicsmentioning
confidence: 99%
“…Listeria monocytogenes, E. coli O157: H7 y Aeromonas hydrophila mostraron una menor capacidad de crecer y sobrevivir en condiciones adversas de almacenamiento cuando fueron previamente tratadas con un tratamiento térmico (Williams y Golden, 2001;Semanchek et al, 1999;Golden et al, 1989), revelando que un tratamiento térmico leve puede ser usado en combinación con otros factores de conservación para el control de patógenos que se transmiten por alimentos en frutas y verduras.…”
Section: Algunos Investigadores Encontraron Que Cepas Patogénicasunclassified